Splenic T2 signal intensity loss on MRI is associated with disease burden in multiple myeloma - Neelsen, Christian; Sachpekidis, Christos; John, Lukas; Neher, Peter; Mai, Elias K.; Grözinger, Martin; Paech, Daniel; Dimitrakopoulou-Strauss, Antonia; Kurz, Felix T.; Sauer, Sandra; Raab, Marc-Steffen; Schlemmer, Heinz-Peter; et al. (European radiology, 2025)
This study aims to evaluate correlations between spleen signal changes in different MRI sequences and bone marrow plasma cell infiltration as potential indicator of disease burden in multiple myeloma (MM) patients.